Characterization of generalized Bessel polynomials in terms of polynomial inequalities - de Andrade, EXL; Dimitrov, D. K.; Ranga, A. S. (Academic Press Inc., 1998)
Generalized Bessel polynomials (GBPs) are characterized as the extremal polynomials in certain inequalities in L-2 norm of Markov type. (C) 1998 Academic Press.